Counting backwards - Kirshenbaum, Binnie (Soho Press, Inc., 2025)
"A middle-aged couple struggles with the husband's descent into early-onset Lewy Body dementia in this profound and deeply moving novel shot through with Kirshenbaum's lacerating humor. It begins with hallucinations. From their living room window, Leo sees a man on stilts, an acting troupe, a pair of swans paddling on the street. Initially, Leo believes the visions are related to visual impairment-they are something he and his wife, Addie, can joke about. Then, he starts to experience occasional, but fleeting, oddities that mimic myriad brain disorders: aphasia, the inability to perform simple tasks, Capgras Syndrome, audial hallucinations he believes to be real. The doctors have no answers. Leo, a scientist, and Addie, a collage artist, had a loving and happy marriage. But as his periods of lucidity become rarer, Addie finds herself less and less able to cope. Eventually, Leo is diagnosed with Lewy Body disease. Life expectancy ranges from 3 to 20 years. A decidedly uncharacteristic act of violence makes it clear that he cannot come home. He moves first to an assisted living facility and then to a small apartment with a caretaker where, over time, he descends into full cognitive decline. Addie's agony, anger, and guilt result in self-imposed isolation, which mirrors Leo's diminished life. And so for years, all she can do is watch him die-too soon, and yet not soon enough. Kirshenbaum captures the couple's final years, months, and days in short scenes that burn with despair, humor, and rage, tracking the brutal destruction of the disease, as well the moments of love and beauty that still exist for them amid the larger tides of loss"--